2007
DOI: 10.1111/j.1365-2222.2007.02680.x
|View full text |Cite
|
Sign up to set email alerts
|

Association and functional relevance of E237G, a polymorphism of the high‐affinity immunoglobulin E‐receptor β chain gene, to airway hyper‐responsiveness

Abstract: In the Korean general population, AHR is significantly associated with the E237G polymorphism of FcepsilonRI-beta, which results in an intolerant amino acid substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…The C-109T polymorphism of MS4A2 encoding the b chain of the high-affinity IgE receptor has been associated with increased plasma IgE levels 7 and the release of proinflammatory factors in asthmatic airways. 8,9 The IL-13 gene is found on chromosome 5q31-33 and has been significantly associated with allergic asthma. 10 The T allele of the IL13 C1923T and IL13 C1112T have both shown to be significantly associated with increased risk of asthma, 11,12 and rs1295686 is involved in the dysregulation of total IgE.…”
Section: Introductionmentioning
confidence: 99%
“…The C-109T polymorphism of MS4A2 encoding the b chain of the high-affinity IgE receptor has been associated with increased plasma IgE levels 7 and the release of proinflammatory factors in asthmatic airways. 8,9 The IL-13 gene is found on chromosome 5q31-33 and has been significantly associated with allergic asthma. 10 The T allele of the IL13 C1923T and IL13 C1112T have both shown to be significantly associated with increased risk of asthma, 11,12 and rs1295686 is involved in the dysregulation of total IgE.…”
Section: Introductionmentioning
confidence: 99%
“…After 1.5 h at −65 °C, the mixture was diluted with Et 2 O (90 mL) and acidified to pH 2-3 with ~60 mL of 1 N HCl, and the phases were separated. The water phase was alkalized to pH 8 with 10 N NaOH and extracted either, and the combined extracts were dried over MgSO 4 83 mmol) in 20 mL of 95% EtOH was added dropwise a solution of sodium borohydride (44 mg, 1.16 mmol) in EtOH (5 mL) at room temperature. The progress of the reaction was monitored by TLC (hexanes/ethyl acetate 1:1).…”
Section: Chemistrymentioning
confidence: 99%
“…fully established, although polymorphisms in genetic loci coding for proteins involved in immune system function are often reported (1)(2)(3)(4). Biological parameters such as increased IgE production, eosinophilia, GATA-3 expression, increases in IL-4, IL-5, IL-10, and tumor necrosis factor-α cytokine production are among a complex array of markers for T H 2-driven immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in several populations have identified various polymorphisms in the MS4A2 gene, including 3 nonsynonymous SNPs in the coding region of the gene [3,4,5,6]. Of these, the 2 coding SNPs (cSNPs) in exon 6 (I181V and V183L) were often absent in certain populations, including the Japanese population, whereas another SNP in exon 7 (E237G) was the more common SNP in this gene [7, 8]. Although a few reports have presented a positive association between the E237G polymorphism and atopic disorders [7, 9], it has been demonstrated by in vitro studies that amino acid variations in the β-chain, including E237G, do not influence the function or the expression of FcεRI [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the 2 coding SNPs (cSNPs) in exon 6 (I181V and V183L) were often absent in certain populations, including the Japanese population, whereas another SNP in exon 7 (E237G) was the more common SNP in this gene [7, 8]. Although a few reports have presented a positive association between the E237G polymorphism and atopic disorders [7, 9], it has been demonstrated by in vitro studies that amino acid variations in the β-chain, including E237G, do not influence the function or the expression of FcεRI [10, 11]. In contrast, another study carried out in the Japanese population identified –426T/C and –654C/T SNPs in the promoter region, in close linkage disequilibrium (LD) with E237G, to directly affect transcriptional activity of the gene [9].…”
Section: Introductionmentioning
confidence: 99%